Strategi Pemasaran Dakwah Digital Dengan Menganalisis Kinerja Iklan Dalam Kampanye Sosial Dan Komersial (Studi Deskriptif Pada Akun @Ayah_Amanah) - Nabila Eka Fitriananda; Dinna Chaerun Nisa; Ahmad Naufal; Pia Khoirotun Nisa (CV. ITTC INDONESIA, 2024)
In the current era, social media has become one of the largest platforms widely used by people throughout the world. Social media is known to make everything easier for people and can be a means for anything, even now social media is used to promote a product to increase sales. Currently, digital da'wah is popular among Muslim communities who use social media. There are many platforms that can be a means of conveying da'wah messages to the public, especially for the current generation who actively use social media. Informing about da'wah or offline studies via social media has also been widely carried out so that people are more interested and knowledgeable and can take part in offline studies easily. This research uses qualitative methods. Qualitative research is research that aims to understand a phenomenon regarding the experiences of research subjects. This is done by describing in the form of words and language, in a certain context naturally and utilizing various natural methods. The results of this research are that influencers and endorsements are marketing strategies used by companies to increase consumer awareness and interest in their products or brands. In a marketing context, influencers and endorsements can be seen as a way to promote a product or brand by using people who have significant influence on the targeted audience. Influencers and endorsements can help increase consumer awareness and interest in a product or brand by featuring the product in their content. Thus, influencers and endorsements can help increase the success of product or brand marketing by promoting the product or brand in an effective and efficient way.